Assisting Students’ Understanding of Memory Location Concept through Visualization - Afiani Mohtar, Itaza; Ahmad, Normah; Nor Hashimah Megat Abdul Rahman, Puteri; Wahijan, Bohari (International Journal of Engineering and Technology, 2018)
Learning programming for the first time is very difficult to many students. This difficulty negatively influences the students’ interest in learning programming thus poses a challenge to the lecturers to maintain students’ active involvement in learning. Students find it difficult to grasp the abstract concept of memory location, thus affects their understanding in writing programs. A memory location simulation program (MeLSim) is proposed to assist students with a realistic and visual experience of the abstract memory location concept. The objectives of this research are to develop a memory location simulation program and to determine students' understanding of the memory location concept after using the simulation. The students were given a pre-test and then required to use MeLSim for two weeks. They were then given a post-test. It was found that, there is significant difference on median total scores before and after using MeLSim. From the results, it can be concluded that students’ using MeLSim improved their test scores. This research provides evidence that visualization can assist students in achieving better understanding of the lessons taught which in turn positively influence their test results.